Making space on the run: exercising the right to move in Jerusalem. Issue 6 (2nd November 2019) - McGahern, Una
ABSTRACT: This paper explores the politics of running in the fragmented city of Jerusalem. Through a series of 'run-alongs' – an innovative method of talking while running – with members of the city's first Palestinian running group, it reveals the mobile, multi-sited and multi-modal practices they use to transgress borders and reclaim spaces for themselves to live within it. Situating an analysis of their running practices within a discussion of the right to the city, it draws attention to social running as a form of collective action and an ongoing exercise of their right to move in the city.